Clinical profile and gram negative bacterial profile of urinary tract infection in children attending a tertiary care hospital of Tamilnadu, India - Balasubramanyam, Vasuki; Sharma, Natwar Lal (International Journal of Contemporary Pediatrics, 2016)
Background: Urinary tract infection (UTI) is one of the most common infections caused by bacterial pathogens seen mostly in developing countries. This study was done to assess the clinical and gram negative bacterial profile of pathogens causing urinary tract infection, which helps the clinician to diagnose early and give presumptive antibiotic to prevent complications. Methods: Specimen was collected in sterile, leak proof container by clean catch mid-stream technique. Isolation of uropathogens was performed by a surface streak procedure on both blood agar and Mac Conkey Agar (Himedia, India) using semi quantitative method by using standard loop technique and Identified as per standard CLSI guidelines. Antibiogram of the isolates was performed and read as per standard manufacturer’s instructions. Results: UTI was more common in female children than male, and half were in the age group 1-5 years. Fever is the most common presentation (58.6%) followed by dysuria (46.4%) abdominal pain (45%) and decreased appetite (23.6%). Escherichia coli was the most common (73.6%) isolate followed in order by Klebsiella sps (15.7%), Citrobacter sps (2.1%) Proteus sps (5%) and Pseudomonas sps (3.5%). Nitrofurantoin (86%) was the most sensitive antibiotic followed by cefexime (84.7%), gentamicin (82%) and ciprofloxacin (81%) for E. coli. Klebsiella was sensitive to gentamycin, ciprofloxacin. Greater degree of resistance was noted to ampicillin, cotrimoxazole and nalidixic acid. Conclusions: The common clinical feature assosciated with UTI was fever and commonest causative organism for UTI was E. coli. The appropriate antibiotic in-vitro were cefexime and gentamicin in this study. Higher degree of resistance was found in antibiotics such as amipicllin, cotrimioxazole, cephalexin, nalidixicacid.